PENGARUH FDI, NET-EKSPOR DAN INFLASI TERHADAP PDB PER KAPITA ASEAN PLUS UPAYA TERLEPAS MIT - Pranada, Alginda Ryan; Sukadana, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 7 (2021): VOL 10 NO 7, JULI 2021 [2661 - 3103], 2021)
The middle income trap, which is an issue in which middle-income countries are stagnant or unable to increase their income into the category of high-income countries. The purpose of this research is to examine foreign direct investment, net exports and inflation with a simultaneous and partial effect on GDP per capita in ASEAN Plus efforts to escape the middle income trap. The research method used is panel data (unbalanced) with the period from 1970-2019. Data analysis technique in this research the chow-test, the Haustman-test, the Lagrange multiplier-test and to test the hypothesis using the partial test (t-test) or simultaneous test (F-test). The results showed foreign direct investment and inflation had no positive impact on GDP per capita in the seven ASEAN Plus countries, meaning that the foreign direct investment and inflation variables were unable to make the country in the study independent from MIT. The results also show that net exports have positive impact on GDP per capita in the seven ASEAN Plus countries. It means that the net export variable is able to increase GDP per capita in the research country so that it can exclude countries from MIT. Keywords ; foreign direct invesment ,net export, inflasi, GDP percapita, production